A new species of Cyclopoliarus (Hemiptera: Auchenorrhyncha: Fulgoromorpha: Cixiidae) from American oil palms (Elaeis oleifera) in Caño Negro, Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Hendrix, Solomon V.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2025)
Recent palm survey work in Costa Rica focusing on planthoppers has resulted in the discovery of several new taxa, primarily in Cixiidae and Derbidae. Here a new species of Cyclopoliarus Fennah, C. nigelwatsoni sp. nov., is described from Caño Negro, Limón Province, Costa Rica. The new species is compared with C. omani, the only other described Central American Cyclopoliarus. Supplemental molecular data is presented for the barcoding region (5’ half) of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and D9 to D10 expansion region of the 28S rRNA gene. A phylogeny is presented to place the new species relative to other available taxa.